2008
DOI: 10.7150/ijbs.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Production & Characterization of a Unique Dextran from an Indigenous Leuconostoc mesenteroides CMG713

Abstract: On the basis of high enzyme activity a newly isolated strain of L. mesenteroides CMG713 was selected for dextran production. For maximum yield of dextran, effects of various parameters such as pH, temperature, sucrose concentration and incubation period were studied. L. mesenteroides CMG713 produced maximum dextran after 20 hours of incubation at 30°C with 15% sucrose at pH 7.0. The molecular mass distribution of dextran produced by this strain showed that its molecular mass was about 2.0 million Da. Dextran a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
2
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 32 publications
6
83
2
7
Order By: Relevance
“…medium (CERNING et al, 1994;SARWAT et al, 2008), both of which require a great amount of medium and glassware. Table 1 shows the result of screening lactic acid bacteria isolated under different growing conditions.…”
Section: Isolation Of Lactic Acid Bacteriamentioning
confidence: 99%
“…medium (CERNING et al, 1994;SARWAT et al, 2008), both of which require a great amount of medium and glassware. Table 1 shows the result of screening lactic acid bacteria isolated under different growing conditions.…”
Section: Isolation Of Lactic Acid Bacteriamentioning
confidence: 99%
“…Among them, the best known are L. casei, L. acidophilus, L.brevis, L. curvatus, L. delbrueckii, L. helveticus, L. rhamnosus, L plantarum and L. johnsonii (5). Dextran (synthesized by certain LAB such as Leuconostoc mesenteroides) was the first microbial polysaccharide to be commercially exploited and to receive authorization for use in foods (6).…”
Section: Introductionmentioning
confidence: 99%
“…Lc. mesenteroides CMG713 produces the highest concentration of dextran after 20 hours of incubation at 30°C in the presence of 15% sucrose at pH 7.0, with an EPS yield of 6 g L -1 (Sarwat et al, 2008). Recently, Capek et al (2011) reported an exceptionally high production of this HoPS (50 g L -1 ) by Lc.…”
Section: Methods Of Productionmentioning
confidence: 99%
“…The depletion of the sucrose source would cause the arrest of the enzymatic reaction of the dextransucrases. It has been reported that high producers of dextran are primarily Leuconostoc, but many other strains of LAB are able to produce this bacterial polysaccharide (Sarwat et al, 2008). The importance of improving its production is related to the industrial applications in the food, pharmaceutical and chemical industries as adjuvant, emulsifier, carrier or stabilizer (Goulas et al, 2004).…”
Section: Methods Of Productionmentioning
confidence: 99%